Examining Vowels' Formant Frequency Shifts Caused by Preceding Consonants for Turkish Language - Korkmaz, Yunus; Boyacı, Aytuğ (Batman Üniversitesi, 2018)
Formant frequency of vowels in a language is considered as one of the important acoustical parameter of speech signal. This parameter can be seen as acoustic resonance of human vocal tract. Although formant frequencies which is changeable across genders, age, and languages have been studied for various purposes by many researchers in some languages, alteration effects of stop consonants on adjacent vowels hasn’t been worked yet for Turkish language. In this study, formant frequency values (F1, F2 and F3) of eight isolated vowels (/a/, /e/, /ı/, /i/, /o/, /ö/, /u/, /ü/) have been compared to formant frequency values of vowels that come after any stop consonant (/p/, /t/, /k/, /b/, /d/, /g/) to detect any changes caused by stop consonants in formant frequencies. Totally 48 meaningful Turkish syllables (combinations of all stop consonants and all vowels) and 8 isolated vowels have been uttered by 10 male speakers three times repeatedly for each unit. At the end of this study, the plosive stop consonants /p/ and /g/ among others have been found as the ones having most alteration effects on F1 value of adjacent vowel /a/ in a CVC-context syllable. F2 of isolated vowel /a/ has been shifted up with /k/ and /g/ visibly. Also, F3 of /a/ has been shifted down by approximately 150 Hz with the same plossive stop consonants /k/ and /g/. These findings can help researchers studying on formant frequencies of vowels in Turkish language in order to specify right syllables to deal with.
Keywords: Engineering; Mühendislik